Application of the Problem Based Learning Model to Increase Students' Confidence in Class V of Al-Wahdah Tolitoli Integrated Islamic Elementary School - Andi Muhammad Abrar (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research is motivated by the phenomenon of low self-confidence of fifth grade students at SD ISLAM TERPADU Al-Wahdah Tolitoli. This study aims to apply a problem-based learning model to increase students' self-confidence in class V SD ISLAM TERPADU Al-Wahdah Tolitoli. This type of research is applied using a qualitative approach. This study consisted of 2 cycles, each cycle consisting of 2 meetings with the stages of activities in the form of planning, implementing, observing, and reflecting. The application of the problem based learning model is the focus of this research in order to increase students' self-confidence. The research subjects totaled 21 students. Data collection techniques using tests, observation, and documentation. The data analysis technique used is descriptive qualitative. The results showed that the application of the Problem Based Learning model by teachers and students' activities in learning were in the good category, for Cycle I and Cycle II. So it can be concluded that the application of the Problem Based Learning model has increased the self-confidence of students in class V SD ISLAM TERPADU Al-Wahdah Tolitoli